HUBUNGAN RIWAYAT PERSALINAN DAN PARITAS DENGAN KEJADIAN PERDARAHAN ANTEPARTUM - Siti Patimah, Siti Patimah; Sitawati (JURNAL SMART ANKes, 2023)
Antepartum hemorrhage is a complication that often occurs in pregnancy until just before delivery. Based on the theory of antepartum hemorrhage, there are several risk factors for pregnant women such as maternal age, parity, history of childbirth, and malnutrition. In 2020, the highest incidence of antepartum hemorrhage in the Kenanga Community Health Center working area was 54 people. This study aims to determine the factors associated with the incidence of antepartum hemorrhage in the Kenanga Community Health Center Work Area in 2023. This research uses an analytical survey research method with a "Case Control" approach with a sample of 52 pregnant women who experienced antepartum hemorrhage and 52 people who did not experience antepartum hemorrhage with a total sample of 104 samples recorded in the Kenanga Community Health Center Work Area in 2023. The results of the study show that parity and birth history are related. with the incidence of antepartum hemorrhage in the Kenanga Community Health Center Work Area in 2023, namely parity (p=0.000 or p < 0.05) and OR=0.194 (there is a relationship and 0.1 times the chance), history of previous birth (p=0.006 or p < 0.05) and OR=0.326 (there is a relationship and 0.3 times the chance). For the Kenanga Community Health Center, it is hoped that the results of this research can be used as consideration in carrying out early detection of high-risk pregnancies and childbirth. This can be carried out by means of scheduled counseling about the high risks of pregnancy which can cause antepartum bleeding. Apart from that, quality pregnancy checks can be carried out with a sufficient number of ANC visits according to standards to monitor the welfare of the mother and baby in her womb Keywords: Parity, Childbirth History, Antepartum.